Efektivitas Penggunaan Gadget Terhadap Anak Usia Dini - Naufal Hafizh Basuki; Muhammad Hafizh Heryanto (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2024)
Technological developments are growing rapidly in line with the times. Technology is an important need today. This is because early childhood education is for children aged 0-6 years, early childhood education has a very important role in developing children's personalities and preparing children to enter a further level of education because technology is needed for many purposes. Technology is very easy to obtain because some prices are cheap and some are expensive according to the user's economic needs. This research uses descriptive research methods, namely by creating a detailed description of the condition of a subject or object. Gadgets are media that are used as modern communication tools. Gadgets make human communication activities easier. Now communication activities have developed even more advanced with the emergence of gadgets. Excessive use of gadgets will have a negative impact on children's social and emotional development. The bad impacts of using gadgets on children include children becoming closed individuals, sleep disorders, liking to be alone, violent behavior, fading creativity, and the threat of cyberbullying. This research uses a descriptive research method, namely by creating a detailed description of the condition of a subject or object. Descriptive research focuses on solving real problems as they existed at the time the research was conducted. In education, descriptive research works more for practical solutions than for the development of science